EXPERIMENTAL AND ANALYTICAL COMPARISON OF TORSION, BENDING MOMENT AND SHEAR FORCES IN REINFORCED CONCRETE BEAMS USING BS 8110, EURO CODE 2 AND ACI 318 PROVISIONS (Nigerian Journal of Technology, 2017)
This study investigated the effect of combined actions of torsional moments, bending moments and shear forces in reinforced concrete beams with concrete compressive strength of 30N/mm2.The ultimate torsional moments, bending moments, and shear forces of the beams were determined experimentally, through a simple test arrangement set-up on fifteen beam specimens grouped from BC1 to BC5, three beam specimens in each group. The combined loads were induced by loading the test beams at an eccentricity of  from the beam’s principal axis at the mid-span, using Computerized Universal Testing Machine TUE-C-100. BS 8110, Euro code 2 and ACI 318 were used to calculate the ultimate torsional moments provided by both longitudinal and transverse reinforcements, bending moments and shear forces induced. The values obtained from the codes were compared with those of experimental results for validation. It was observed that Eurocode 2 predicted the highest bending moment of 21.1530kNm, the highest torsional moments of 9.8470kNm and 12.6193kNm, for torsional resistance provided by longitudinal and transverse reinforcements respectively, at an angle crack of 45°, while BS 8110 predicted the least values. ACI 318 predicted the highest value of internal shear forces that the beams possessed before yielding to the applied loads. http://dx.doi.org/10.4314/njt.v36i3.7